Lalake po ako Life stories of men who have sex with men - De los Santos, Rhoda E.; Labaclado, Richie D.; Pelonia, Alexandra Mari N. (Tacloban City Rhoda E. De los Santos, 2013)
This study explored the life stories of men who have sex with men (MSM). With the depth, quality and complexity of the participants' subjective reality, the researchers were able to explore their behaviors, perspectives, feelings, and experiences. A qualitative research design was used in this study with 5 MSM participants recruited using a non-probability purposive sampling and interviewed using a semi-structured interview questionnaire. Individual factors such as the participant's personal beliefs about MSM phenomenon, their personal evaluation of the consequences of the behavior and the normative factors including beliefs about their parents and friends perception about MSM was found to have a great influence on their decision to engage in same-sex activities. Interestingly, despite the negative perception that the parents have towards same-sex activities, participants still engaged in sexual activities with the same-sex citing curiosity, peer influence, satisfaction of material and sexual needs as push factors. In addition, participants clearly identified the stigmatized labels that most people have towards those who engage in same sex activities. Moreover, dissonance seems not to exist between the sexual behaviors and sexual orientation of the participants which acknowledges the fact that engaging in MSM does not make one homosexual nor does it imply a change in sexual orientation. The stories of these MSM are not ordinary, and should therefore be known to correct the misconceptions about them, and broaden the perspective of Filipinos about sexuality.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban.
Keywords: Social Science